Method for producing N-alkylmaleimide copolymer, and N-alkylmaleimide copolymer
By using a specific polymerization solvent to perform precipitation polymerization in the copolymer of N-alkylmaleimide and styrene compounds, the problem that the copolymer is easily adhered to the equipment during the precipitation polymerization process is solved, and high-efficiency manufacturing is achieved with excellent results N-alkyl maleimide-based copolymer with optical properties and heat resistance.
Patent Information
- Application Number
- CN202380048572.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-29
- Filing Date
- 2023-06-29
- Publication Date
- 2025-02-07
AI Technical Summary
In the prior art, copolymers of N-alkylmaleimide and styrene compounds are prone to copolymers attached to the inner wall of stirred blades and polymerization vessels during precipitation polymerization, resulting in production blockage and difficulty in removing unreacted monomers and Impurities affect the transparency of the copolymer.
Precipitation polymerization is carried out using a specific polymerization solvent to allow the monomer of N-alkylmaleimide and styrene compound to be radically copolymerized in solution to form a copolymer precipitated in particle form, thereby facilitating the removal of impurities and improving copolymerization. Transparency of objects.
Through this method, a large number of N-alkyl maleimide-based copolymers with excellent optical properties and heat resistance can be efficiently produced, and blockage problems in the production process can be avoided, and the fluidity of the copolymer during molding is improved. .
Smart Images

Figure BDA0005199359790000031 
Figure BDA0005199359790000032 
Figure BDA0005199359790000041
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing an N-alkylmaleimide-based copolymer and an N-alkylmaleimide-based copolymer, wherein the N-alkylmaleimide-based copolymer comprises a structural unit derived from an N-alkylmaleimide and a styrene compound. More specifically, the present invention relates to a method for efficiently producing an N-alkylmaleimide-based copolymer, wherein the copolymer has excellent optical properties and heat resistance, and an N-alkylmaleimide-based copolymer, wherein the copolymer has excellent optical properties, heat resistance, and fluidity during molding. Background Art
[0002] It is known that copolymers obtained from N-alkylmaleimide (N-alkylmaleimide copolymers) have high heat resistance and are resins with better transparency than general thermoplastic ethylene polymers. Therefore, N-alkylmaleimide copolymers are promising materials as transparent resins that can be used in various applications in the optical field. (For example, refer to Non-Patent Document 1).
[0003] Furthermore, it is reported that an N-alkylmaleimide-based copolymer containing an N-alkylmaleimide and a styrene compound is a polymer material that can achieve low birefringence with a simple composition and can maintain low birefringence in a wide range of ambient temperatures (for example, refer to Patent Document 1).
[0004] N-alkylmaleimide copolymers can be manufactured by free radical polymerization. In addition, the manufacturing method can be manufactured by previously known methods such as block polymerization, emulsion polymerization, suspension polymerization, and solution polymerization. However, the copolymer generated in the block polymerization is a block, and it is difficult to remove the unreacted monomers, so there is a problem that the transparency of the generated copolymer is impaired. In addition, the generated copolymer is a high molecular weight body, and contains a copolymer component with a high N-alkylmaleimide content and low strength, and exhibits flow characteristics during molding. Therefore, when a chain transfer agent is added to the material of the generated copolymer to make the generated copolymer low molecular weight, there is a problem that the strength of the generated copolymer decreases. In the case of emulsion polymerization and suspension polymerization, it is difficult to remove the emulsifier and dispersant respectively. On the other hand, in the solution polymerization in which the copolymer is dissolved in the polymerization solvent and not precipitated in the form of particles, for example, by precipitating and purifying the generated copolymer solution after polymerization in a poor solvent, a copolymer with relatively good transparency can be obtained. However, it is difficult to purify the polymer industrially by such a reprecipitation method, and there is also a problem of complicated manufacturing process, so it is impractical.
[0005] In this regard, a method for producing N-alkylmaleimide copolymers has been reported: a polymerization solvent is used for polymerization, the monomers are dissolved in the solvent, but the resulting copolymers are not dissolved and precipitate in the form of particles, i.e., a method of producing by precipitation polymerization. (For example, refer to patent documents 2 to 4). It is believed that by using these methods, impurities such as unreacted monomers or their modified products that affect the transparency of the resulting copolymers are dissolved in the polymerization solvent. Therefore, by separating the copolymer particles generated by the polymerization solvent, the above impurities can be easily removed, thereby obtaining N-alkylmaleimide copolymers with good transparency.
[0006] Furthermore, the methods represented by Patent Documents 2 to 4 are excellent in that copolymers having particularly excellent optical properties can be obtained because they do not involve an emulsifier or a dispersant used in ordinary emulsion polymerization or suspension polymerization.
[0007] Furthermore, in the methods represented by Patent Documents 2 to 4, since the produced copolymer can be obtained in the form of particles, the production process such as the separation step from the solvent and the drying step can be simplified.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2020-126229
[0011] Patent Document 2: Japanese Patent Application Laid-Open No. 5-194609
[0012] Patent Document 3: Japanese Patent Application Laid-Open No. 5-209004
[0013] Patent Document 4: Japanese Patent Application Laid-Open No. 5-247145
[0014] Non-patent literature
[0015] Non-patent document 1: Otsu Takayuki, "Future Materials", Vol. 3, No. 1, pp. 74-79 Summary of the invention
[0016] Problems to be solved by the invention
[0017] However, in the methods represented by Patent Documents 2 to 4, precipitation polymerization in the copolymerization of N-alkylmaleimide and styrene compound does not proceed smoothly, and there are production problems such as adhesion of copolymer to stirring blades and the inner wall of the polymerization container, resulting in clogging.
[0018] In view of the above problems, the present invention aims to provide a method for efficiently producing an N-alkylmaleimide-based copolymer having excellent optical properties and heat resistance, and to provide an N-alkylmaleimide-based copolymer having excellent optical properties, heat resistance and fluidity during molding.
[0019] Solutions to the problem
[0020] In order to solve the above-mentioned problems, the present inventors have conducted intensive research and found a method for producing an N-alkylmaleimide-based copolymer based on precipitation polymerization, and an N-alkylmaleimide-based copolymer having a specific structure, wherein the precipitation polymerization uses a specific polymerization solvent, thereby completing the present invention.
[0021] In order to solve the above problems, a method for producing an N-alkylmaleimide copolymer according to one embodiment of the present invention comprises: subjecting a monomer comprising 20 to 95% by weight of an N-alkylmaleimide represented by the following formula (1) and 5 to 80% by weight of a styrene compound to free radical copolymerization, wherein when producing the N-alkylmaleimide copolymer, the monomer is free radical copolymerized in a polymerization solvent in which the monomer is dissolved and the generated N-alkylmaleimide copolymer is precipitated in the form of particles, wherein the N-alkylmaleimide copolymer has structural units derived from the N-alkylmaleimide and the styrene compound. In formula (1), R 1 It represents a linear alkyl group having 1 to 12 carbon atoms, a branched alkyl group having 3 to 12 carbon atoms, or a cycloalkyl group having 3 to 6 carbon atoms.
[0022]
[0023] In addition, in order to solve the above-mentioned problems, an N-alkylmaleimide-based copolymer of one embodiment of the present invention comprises: 30 to 70 wt % of an N-alkylmaleimide-based structural unit represented by formula (2), 10 to 40 wt % of a styrene-based structural unit, and 10 to 40 wt % of a (meth)acrylate-based structural unit, and the N-alkylmaleimide-based copolymer satisfies the following conditions (a) and (b).
[0024] (a) Glass transition point (Tg) is 120-180°C;
[0025] (b) The weight average molecular weight (Mw) is 200,000 to 500,000.
[0026]
[0027] In formula (2), R 1It represents a linear alkyl group having 1 to 12 carbon atoms, a branched alkyl group having 3 to 12 carbon atoms, or a cycloalkyl group having 3 to 6 carbon atoms.
[0028] Effects of the Invention
[0029] The production method of the present invention can efficiently produce an N-alkylmaleimide copolymer having excellent optical properties and heat resistance. Furthermore, by using the N-alkylmaleimide copolymer of the present invention, an N-alkylmaleimide copolymer having excellent fluidity during molding can be obtained. DETAILED DESCRIPTION
[0030] Hereinafter, each aspect of the present invention will be described in detail. It should be noted that the numerical range represented by "to" in this specification is a range including the numerical values recorded before and after "to" as the minimum value and the maximum value, respectively.
[0031] A method for producing a copolymer according to one embodiment of the present invention comprises subjecting a monomer comprising 20 to 95% by weight of an N-alkylmaleimide represented by the following formula (1) and 5 to 80% by weight of a styrene compound to radical copolymerization to produce an N-alkylmaleimide-based copolymer having a structural unit derived from the N-alkylmaleimide and a styrene compound.
[0032]
[0033] [N-Alkylmaleimide]
[0034] In formula (1), R 1 It represents a straight-chain alkyl group having 1 to 12 carbon atoms, a branched-chain alkyl group having 3 to 12 carbon atoms, or a cycloalkyl group having 3 to 6 carbon atoms. Examples of the straight-chain alkyl group having 1 to 12 carbon atoms include methyl, ethyl, propyl, butyl, pentyl, hexyl, octyl, decyl, and dodecyl. Examples of the branched-chain alkyl group having 3 to 12 carbon atoms include isopropyl, isobutyl, sec-butyl, and tert-butyl. Examples of the cycloalkyl group having 3 to 6 carbon atoms include cyclopropyl, cyclobutyl, and cyclohexyl.
[0035] Among them, from the viewpoint of further improving the heat resistance of the obtained N-alkylmaleimide copolymer, R 1 Preferred is methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, hexyl, cyclohexyl or octyl, and more preferred is methyl, ethyl, isopropyl, tert-butyl or cyclohexyl.
[0036] In addition, since the N-alkylmaleimide compound has a low impact on the surrounding environment and the equipment can be simplified, R 1 An ethyl group, a tert-butyl group or a cyclohexyl group is preferred. The N-alkylmaleimide represented by the formula (1) may be used alone or in combination of two or more.
[0037] Specific examples of the N-alkylmaleimide represented by formula (1) include N-methylmaleimide, N-ethylmaleimide, N-propylmaleimide, N-isopropylmaleimide, N-butylmaleimide, N-isobutylmaleimide, N-sec-butylmaleimide, N-tert-butylmaleimide, N-pentylmaleimide, N-hexylmaleimide, N-octylmaleimide, N-decylmaleimide, N-dodecylmaleimide, N-cyclopropylmaleimide, N-cyclobutylmaleimide and N-cyclohexylmaleimide. Among them, from the viewpoint of obtaining an N-alkylmaleimide copolymer having better heat resistance, the N-alkylmaleimide represented by formula (1) is preferably N-methylmaleimide, N-ethylmaleimide, N-isopropylmaleimide, N-tert-butylmaleimide or N-cyclohexylmaleimide. Furthermore, since the compound of N-alkylmaleimide has a low impact on the surrounding environment, the N-alkylmaleimide copolymer can be efficiently and economically produced using simpler equipment. From this viewpoint, the N-alkylmaleimide represented by formula (1) is more preferably N-ethylmaleimide, N-tert-butylmaleimide or N-cyclohexylmaleimide.
[0038] [Styrene compounds]
[0039] The styrene compound of one embodiment of the present invention is a general term for styrene and its derivatives, and is not limited as long as it is a monomer having a styrene skeleton. Among the styrene compounds, alkyl styrene, halogenated styrene, alkoxy styrene and styrene can be exemplified. As for alkyl styrene, o-methyl styrene, m-methyl styrene, p-methyl styrene, o, p-dimethyl styrene, o-ethyl styrene, m-ethyl styrene, p-ethyl styrene and α-methyl styrene can be cited. As for halogenated styrene, o-fluorostyrene, m-fluorostyrene, p-fluorostyrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, o-bromostyrene, m-bromostyrene and p-bromostyrene can be cited. As for alkoxystyrene, o-methoxystyrene, m-methoxystyrene, p-methoxystyrene, o-ethoxystyrene, m-ethoxystyrene and p-ethoxystyrene can be cited. Among them, from the perspective of obtaining an N-alkylmaleimide copolymer with better optical properties, the styrene compound is preferably styrene or α-methylstyrene. As the styrene compound, only one kind may be used or a plurality of kinds may be mixed and used.
[0040] [Monomer content]
[0041] The monomer in one embodiment of the present invention comprises an N-alkylmaleimide represented by formula (1) and a styrene compound. The content of N-alkylmaleimide in the monomer is 20 to 97% by weight, and the content of styrene compound is 3 to 80% by weight. Among them, from the perspective of being able to obtain an N-alkylmaleimide copolymer having particularly excellent heat resistance and optical properties, the content of N-alkylmaleimide in the monomer is preferably 35 to 97% by weight, more preferably 50 to 97% by weight. For the same reason, the content of styrene compound in the monomer is preferably 3 to 65% by weight, more preferably 3 to 50% by weight. In addition, from the perspective of obtaining an N-alkylmaleimide copolymer having a better photoelastic modulus and intrinsic birefringence, the content of N-alkylmaleimide in the above monomer is 55 to 80% by weight, and the content of styrene compound is preferably 20 to 45% by weight.
[0042] [Other monomers]
[0043] In addition, with respect to the embodiments of the present invention, other copolymerizable monomers may be copolymerized if necessary. As other copolymerizable monomers, there is no limitation as long as they can be copolymerized with N-alkylmaleimide. As for other copolymerizable monomers, examples include: olefins, alkyl acrylates, alkyl methacrylates and vinyl carboxylates. As for olefins, ethylene, propylene, 1-butene and isobutylene may be mentioned. As for alkyl acrylates, methyl acrylate, ethyl acrylate and butyl acrylate may be mentioned. As for alkyl methacrylates, methyl methacrylate, ethyl methacrylate and butyl methacrylate may be mentioned. As for vinyl carboxylates, vinyl acetate, vinyl propionate and vinyl pivalate may be mentioned.
[0044] Among them, from the viewpoint of realizing low birefringence with a simple composition and maintaining its low birefringence in a wide range of ambient temperatures (e.g., 0 to 80° C.), other copolymerizable monomers are preferably alkyl acrylates such as methyl acrylate or alkyl methacrylates such as methyl methacrylate. Other copolymerizable monomers may be used alone or in combination of two or more.
[0045] [Polymerization method]
[0046] In an embodiment of the present invention, an N-alkylmaleimide copolymer is produced by precipitation polymerization using the above-mentioned monomer as a raw material. That is, in an embodiment of the present invention, the above-mentioned monomer is dissolved and free radical copolymerized in a polymerization solvent in which the generated N-alkylmaleimide copolymer is precipitated in the form of particles.
[0047] [Polymerization solvent]
[0048] As the polymerization solvent used in the manufacturing method of one embodiment of the present invention, as long as it can dissolve the monomer, the N-alkylmaleimide copolymer is insoluble, and the generated N-alkylmaleimide copolymer can be precipitated in the form of particles, there is no limitation. Among the polymerization solvents, examples include: aliphatic hydrocarbons, aromatic hydrocarbons, water-soluble organic solvents, ketone organic solvents, ester organic solvents and water. As for aliphatic hydrocarbons, propane, butane, isobutane, hexane, methylcyclohexane and octane can be mentioned. As for aromatic hydrocarbons, benzene, toluene and xylene can be mentioned. As for water-soluble organic solvents, methanol, ethanol, propanol, isopropanol, acetone and acetonitrile can be mentioned. As for ketone organic solvents, ketone organic solvents other than acetone can be mentioned, and methyl ethyl ketone and methyl isobutyl ketone can be mentioned. As for ester organic solvents, ethyl acetate, butyl acetate, dimethyl carbonate, diethyl carbonate and propylene carbonate can be mentioned. These polymerization solvents may be used alone or in combination of two or more.
[0049] Among them, from the viewpoint that a particulate N-alkylmaleimide copolymer can be obtained with a higher yield, the polymerization solvent is preferably a mixed solvent comprising a water-soluble organic solvent and water, or a mixed solvent comprising an aliphatic hydrocarbon and an ester organic solvent. The polymerization solvent is further preferably a mixed solvent of methanol and water, a mixed solvent of methylcyclohexane and dimethyl carbonate, or a mixed solvent of methylcyclohexane and butyl acetate. The polymerization solvent is particularly preferably a mixed solvent of methanol and water.
[0050] When the polymerization solvent is a mixed solvent comprising a water-soluble organic solvent and water, the mixing ratio of the water-soluble organic solvent and water is not particularly limited. From the viewpoint of obtaining a particulate N-alkylmaleimide copolymer with a higher yield, the content of the water-soluble organic solvent in the polymerization solvent is preferably 50 to 98% by weight, and the content of water is preferably 2 to 50% by weight. For the same reason, the content of the water-soluble organic solvent in the polymerization solvent is more preferably 75 to 97% by weight, and further preferably 80 to 95% by weight. In addition, for the same reason, the content of water in the polymerization solvent is more preferably 3 to 25% by weight, and further preferably 5 to 20% by weight.
[0051] When the polymerization solvent is a mixed solvent of an aliphatic hydrocarbon and an ester organic solvent, the mixing ratio of the aliphatic hydrocarbon and the ester organic solvent is not particularly limited. From the viewpoint of obtaining a particulate N-alkylmaleimide copolymer in a higher yield, the content of the aliphatic hydrocarbon in the polymerization solvent is preferably 50 to 98% by weight, and the content of the ester organic solvent is preferably 2 to 50% by weight. For the same reason, the content of the aliphatic hydrocarbon in the polymerization solvent is more preferably 55 to 95% by weight, and further preferably 60 to 90% by weight. In addition, for the same reason, the content of the ester organic solvent in the polymerization solvent is more preferably 5 to 45% by weight, and further preferably 10 to 40% by weight.
[0052] [Polymerization initiator]
[0053] In the manufacturing method of one embodiment of the present invention, a free radical polymerization initiator can be used. Among the free radical polymerization initiators, a fat-soluble free radical polymerization initiator is preferably used. As fat-soluble free radical polymerization initiators, organic peroxides and azo initiators can be exemplified. As for organic peroxides, benzoyl peroxide, dodecyl peroxide, octanoyl peroxide, acetyl peroxide, di-tert-butyl peroxide, tert-butyl peroxide isopropylbenzene, diisopropylbenzene peroxide, tert-butyl peroxyacetate, tert-butyl peroxybenzoate, tert-butyl peroxy-2-ethylhexanoate, tert-hexyl peroxy-2-ethylhexanoate, 2,5-dimethyl-2,5-di(2-ethylhexanoyl peroxide)hexane, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexyl ester, tert-butyl peroxypivalate, tert-hexyl peroxypivalate, tert-butyl peroxyneodecanoate and tert-hexyl peroxyneodecanoate can be cited. Examples of the azo initiator include 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-butyronitrile), 2,2'-azobisisobutyronitrile, dimethyl-2,2'-azobisisobutyl ester, and 1,1'-azobis(cyclohexane-1-carbonitrile).
[0054] The amount of the fat-soluble radical polymerization initiator used can be appropriately set. For example, the amount of the fat-soluble radical polymerization initiator used can be 0.0001 to 2 parts by weight relative to 100 parts by weight of the total amount of the monomers. Among them, in particular, from the viewpoint of being able to obtain an N-alkylmaleimide copolymer with better optical properties and mechanical strength, the amount of the fat-soluble radical polymerization initiator used is preferably 0.001 to 1 part by weight, and more preferably 0.01 to 0.5 part by weight.
[0055] [Polymerization temperature]
[0056] The polymerization temperature of one embodiment of the production method of the present invention can be appropriately set according to the decomposition temperature of the fat-soluble free radical polymerization initiator. In particular, from the viewpoint of efficiently producing an N-alkylmaleimide copolymer having excellent optical properties and mechanical strength, the polymerization temperature is preferably in the range of 10 to 80° C., more preferably in the range of 20 to 70° C., and particularly preferably in the range of 30 to 60° C.
[0057] [Cleaning]
[0058] In the production method of one embodiment of the present invention, from the viewpoint of efficiently and economically producing an N-alkylmaleimide-based copolymer having excellent optical properties and mechanical strength in the form of particles, after filtering the particles of the N-alkylmaleimide-based copolymer obtained by precipitation polymerization, the particles are preferably washed with a washing solvent.
[0059] The cleaning solvent is not limited as long as it is a solvent that does not dissolve the N-alkylmaleimide copolymer but dissolves the unreacted monomer. Examples of the cleaning solvent include water, methanol, ethanol, a methanol / toluene mixed solvent, an ethanol / toluene mixed solvent, a methanol / water mixed solvent, and an ethanol / water mixed solvent. For example, in water, the unreacted N-alkylmaleimide monomer is soluble. On the other hand, in methanol, ethanol, a methanol / toluene mixed solvent, an ethanol / toluene mixed solvent, a methanol / water mixed solvent, and an ethanol / water mixed solvent, both the unreacted N-alkylmaleimide and the unreacted styrene compound are soluble.
[0060] [Other additives]
[0061] In one embodiment of the present invention, a chain transfer agent such as alkyl mercaptan, or a hindered phenol-based or phosphorus-based antioxidant may be used as necessary at the initial stage of polymerization, during polymerization, or after polymerization.
[0062] One embodiment of the present invention generates an N-alkylmaleimide copolymer by polymerization reaction, thereby obtaining particles of the copolymer. In one embodiment of the present invention, an emulsifier or dispersant for improving the dispersion stability of the particles may not be used. Therefore, in one embodiment of the present invention, no emulsifier or dispersant for the above purpose is added to the raw material composition (monomer mixture) of the polymerization reaction.
[0063] [Characteristics of N-alkylmaleimide copolymers]
[0064] The N-alkylmaleimide copolymer obtained by the manufacturing method according to one embodiment of the present invention is in the form of particles. By efficiently removing the polymerization solvent, or the unreacted monomer, or both, an N-alkylmaleimide copolymer having excellent optical properties and mechanical strength can be obtained. The polymerization solvent or the unreacted monomer is efficiently removed, and an N-alkylmaleimide copolymer having excellent optical properties and mechanical strength is obtained. From the above viewpoints, the average particle size of the particles of the N-alkylmaleimide polymer generated in the polymerization solvent is preferably 20 to 2000 μm, more preferably 30 to 1000 μm, and further preferably 50 to 900 μm. It should be noted that the average particle size in this specification is obtained by laser diffraction / scattering method, and the particle size when the cumulative particle amount based on volume is 50%. The average particle size can be adjusted according to the classification of the particles and the mixing of the classified products, and can also be adjusted according to the stirring speed, polymerization solvent and monomer content in precipitation polymerization.
[0065] The amount of attachments contained in the N-alkylmaleimide copolymer obtained by the manufacturing method according to one embodiment of the present invention is represented by the attachment yield. The attachment yield is represented by the following method: after polymerization, the copolymer attached to the stirring blade and the inner wall of the polymerization container is recovered, and the weight of the attachments is obtained by washing and drying, and the weight of the attachments obtained is divided by the total weight of the added monomers to obtain the weight %. In terms of the manufacturing method according to one embodiment of the present invention, the attachment yield becomes smaller, preferably less than 51% by weight, more preferably less than 40% by weight, particularly preferably less than 20% by weight, and more particularly preferably less than 10% by weight. The attachment yield can be controlled by the polymerization solvent composition, the added monomer composition, the added monomer concentration or the polymerization temperature.
[0066] [N-Alkylmaleimide Copolymer Obtained by the Production Method]
[0067] The weight average molecular weight (M) of the N-alkylmaleimide copolymer obtained by the production method according to one embodiment of the present invention is w ) is not particularly limited. From the viewpoint of obtaining an N-alkylmaleimide copolymer having excellent optical properties and mechanical strength, the weight average molecular weight of the N-alkylmaleimide copolymer is preferably 100,000 to 2,000,000, more preferably 150,000 to 1,800,000, and particularly preferably 200,000 to 1,500,000.
[0068] The glass transition point (Tg) of the N-alkylmaleimide copolymer obtained by the manufacturing method according to one embodiment of the present invention is an indicator of heat resistance. The glass transition point (Tg) of the N-alkylmaleimide copolymer obtained by one embodiment of the manufacturing method of the present invention is not particularly limited. From the perspective of being able to obtain an N-alkylmaleimide copolymer with excellent heat resistance, the glass transition point is preferably 120°C or more, more preferably 135°C or more, and particularly preferably 150°C or more.
[0069] The tensile stress of the N-alkylmaleimide copolymer obtained by the manufacturing method according to one embodiment of the present invention is an indicator of mechanical strength. The tensile stress of the N-alkylmaleimide copolymer obtained by one embodiment of the manufacturing method of the present invention is not particularly limited. From the perspective of being able to obtain an N-alkylmaleimide copolymer with excellent mechanical strength, the tensile stress is preferably 30 MPa or more, more preferably 35 MPa or more, and particularly preferably 40 MPa or more. It should be noted that the tensile stress of the N-alkylmaleimide copolymer is measured by M w Take control.
[0070] The tensile elongation is not particularly limited as an index of the mechanical strength of the N-alkylmaleimide copolymer obtained by the production method according to one embodiment of the present invention. From the perspective of obtaining an N-alkylmaleimide copolymer having excellent mechanical strength, the tensile elongation is preferably 2% or more, more preferably 2.5% or more, and particularly preferably 3% or more.
[0071] The haze of the N-alkylmaleimide copolymer obtained by the manufacturing method according to one embodiment of the present invention is one of the indicators of optical properties. The haze of the N-alkylmaleimide copolymer obtained by one embodiment of the manufacturing method of the present invention is not particularly limited. From the perspective of obtaining an N-alkylmaleimide copolymer with excellent transparency, the haze is preferably less than 3%, more preferably less than 2.5%, and particularly preferably less than 2%. It should be noted that the haze of the N-alkylmaleimide copolymer can be controlled by the residual amount of the monomer.
[0072] The photoelastic constant (C) and intrinsic birefringence (Δn) of the N-alkylmaleimide copolymer obtained by the production method according to one embodiment of the present invention are 0 ) is one of the indicators of optical properties. The photoelastic constant (C) and intrinsic birefringence (Δn) of the N-alkylmaleimide copolymer obtained according to one embodiment of the production method of the present invention are 0 ) are not particularly limited. From the perspective of obtaining a low-birefringence N-alkylmaleimide copolymer, the absolute value of the photoelastic constant of the N-alkylmaleimide copolymer is preferably 50×10 -12 Pa -1 Less than, more preferably 10×10 -12 Pa -1 Below, more preferably 2×10 -12 Pa -1 For the same reason, the absolute value of the intrinsic birefringence of the N-alkylmaleimide copolymer is preferably 20×10 -3 Less than, more preferably 5×10 -3 Below, more preferably 1×10 -3 It should be noted that the C and Δn of the N-alkylmaleimide copolymer 0 The ratio can be controlled by the type of monomer and the ratio of the monomer units in the N-alkylmaleimide copolymer.
[0073] The temperature constant (dΔn) of the intrinsic birefringence of the N-alkylmaleimide copolymer obtained by the production method according to one embodiment of the present invention is 0 / dT) is one of the indices of optical properties. The temperature constant (dΔn) of the intrinsic birefringence of the N-alkylmaleimide copolymer obtained according to one embodiment of the production method of the present invention is 0 / dT), the absolute value of which is not particularly limited. In view of being able to obtain an N-alkylmaleimide copolymer that can maintain low birefringence in a wide range of ambient temperatures, the temperature constant is preferably 2×10 -5 ℃ -1 Below, more preferably 1×10 -5 ℃ -1 It should be noted that the dΔn of the N-alkylmaleimide copolymer 0 / dT can be controlled by the type of monomer and the ratio of the monomer units in the N-alkylmaleimide-based copolymer.
[0074] [N-Alkylmaleimide copolymer]
[0075] Another embodiment of the present invention is an N-alkylmaleimide copolymer comprising: 30 to 70% by weight of an N-alkylmaleimide structural unit represented by formula (2), 10 to 40% by weight of a styrene structural unit, and 10 to 40% by weight of a (meth)acrylate structural unit. The N-alkylmaleimide copolymer satisfies the following conditions (a) and (b), and can be produced, for example, by the method for producing an N-alkylmaleimide copolymer according to one embodiment of the present invention.
[0076] (a) Glass transition point (Tg) is 120-180°C;
[0077] (b) The weight average molecular weight (Mw) is 200,000 to 500,000.
[0078]
[0079] The N-alkylmaleimide structural unit refers to a repeating unit having the same structure as the structure of the N-alkylmaleimide of formula (1) in a radical copolymer derived from the N-alkylmaleimide. The styrene structural unit refers to a repeating unit having the same structure as the structure of a styrene compound in a radical copolymer derived from a styrene compound (styrene or its derivative). The (meth)acrylate structural unit refers to a repeating unit having the same structure as the structure of a (meth)acrylate compound in a radical copolymer derived from a (meth)acrylate compound ((meth)acrylate or its derivative).
[0080] R in formula (2) 1 An example of R in formula (1) is 1Specific examples of the N-alkylmaleimide structural unit represented by formula (2) include: N-methylmaleimide unit, N-ethylmaleimide unit, N-propylmaleimide unit, N-isopropylmaleimide unit, N-butylmaleimide unit, N-isobutylmaleimide unit, N-sec-butylmaleimide unit, N-tert-butylmaleimide unit, N-pentylmaleimide unit, N-hexylmaleimide unit, N-octylmaleimide unit, N-decylmaleimide unit, N-dodecylmaleimide unit, N-cyclopropylmaleimide unit, N-cyclobutylmaleimide unit and N-cyclohexylmaleimide unit. Among them, from the viewpoint of obtaining an N-alkylmaleimide copolymer with better heat resistance, the N-alkylmaleimide structural unit represented by formula (2) is preferably an N-methylmaleimide unit, an N-ethylmaleimide unit, an N-isopropylmaleimide unit, an N-tert-butylmaleimide unit, or an N-cyclohexylmaleimide unit. In addition, since the compound as an N-alkylmaleimide has a low impact on the surrounding environment, the N-alkylmaleimide copolymer can be efficiently and economically produced with a more simplified equipment. From the above viewpoint, the N-alkylmaleimide structural unit represented by formula (2) is more preferably an N-ethylmaleimide unit, an N-tert-butylmaleimide unit, or an N-cyclohexylmaleimide unit.
[0081] Examples of the styrene structural unit include an alkylstyrene unit, a halogenated styrene unit, an alkoxystyrene unit, and a styrene unit. As for the alkylstyrene unit, examples include an o-methylstyrene unit, an m-methylstyrene unit, a p-methylstyrene unit, an o,p-dimethylstyrene unit, an o-ethylstyrene unit, an m-ethylstyrene unit, a p-ethylstyrene unit, and an α-methylstyrene unit. As for the halogenated styrene unit, examples include an o-fluorostyrene unit, an m-fluorostyrene unit, a p-fluorostyrene unit, an o-chlorostyrene unit, an m-chlorostyrene unit, a p-chlorostyrene unit, an o-bromostyrene unit, an m-bromostyrene unit, and a p-bromostyrene unit. As for the alkoxystyrene unit, examples include an o-methoxystyrene unit, an m-methoxystyrene unit, a p-methoxystyrene unit, an o-ethoxystyrene unit, an m-ethoxystyrene unit, and a p-ethoxystyrene unit. Among them, from the viewpoint of obtaining an N-alkylmaleimide copolymer having better optical properties, the styrene structural unit is preferably a styrene unit or an α-methylstyrene unit. As the styrene compound unit, only one kind thereof may be used or a plurality of kinds thereof may be mixed and used.
[0082] As for the (meth)acrylate structural unit, there can be mentioned: alkyl acrylate unit and alkyl methacrylate unit. Among the alkyl acrylate units, there can be mentioned: methyl acrylate unit, ethyl acrylate unit and butyl acrylate unit. Among the alkyl methacrylate units, there can be mentioned: methyl methacrylate unit, ethyl methacrylate unit and butyl methacrylate unit. Among them, from the viewpoint of realizing low birefringence with a simple composition and maintaining its low birefringence in a wide range of ambient temperatures (for example, 0 to 80° C.), the (meth)acrylate structural unit is preferably a methyl acrylate unit or a methyl methacrylate unit.
[0083] In addition, if necessary, the N-alkylmaleimide copolymer can contain other copolymerizable monomer units. As other copolymerizable monomer units, there is no limitation as long as they can be copolymerized with N-alkylmaleimide. Among other copolymerizable monomer units, for example, olefin units and carboxylic acid vinyl ester units can be exemplified. Among the olefin units, ethylene units, propylene units, 1-butene units and isobutylene units can be cited. Among the carboxylic acid vinyl ester units, vinyl acetate units, vinyl propionate units and vinyl pivalate units can be cited.
[0084] In the N-alkylmaleimide copolymer of one embodiment of the present invention, the ratio of the N-alkylmaleimide structural unit represented by formula (2) is 30 to 70% by weight, the styrene structural unit is 10 to 40% by weight, and the (meth)acrylate structural unit is 10 to 40% by weight. Among them, from the perspective of obtaining an N-alkylmaleimide copolymer having excellent heat resistance and optical properties, the ratio is preferably 40 to 60% by weight of the N-alkylmaleimide structural unit represented by formula (2), 20 to 30% by weight of the styrene structural unit, and 20 to 30% by weight of the (meth)acrylate structural unit.
[0085] From the viewpoint of exhibiting excellent mechanical properties in addition to excellent optical properties, the Mw (b) of the N-alkylmaleimide copolymer of another embodiment of the present invention is preferably 200000 or more. In addition, from the viewpoint of exhibiting excellent fluidity during molding in addition to excellent optical properties, the Mw is preferably 500000 or less, more preferably 450000 or less, and particularly preferably 400000 or less.
[0086] In another embodiment of the present invention, from the viewpoint of having excellent fluidity during molding in addition to excellent optical properties and mechanical strength, the (b) Mw range of the N-alkylmaleimide copolymer is preferably 200,000 to 500,000, more preferably 200,000 to 450,000, and particularly preferably 200,000 to 400,000.
[0087] It should be noted that the weight average molecular weight (M w ) can be controlled by monomer concentration, polymerization solvent or polymerization temperature.
[0088] In another embodiment of the present invention, from the viewpoint of exhibiting excellent heat resistance, the (a) Tg of the N-alkylmaleimide copolymer is preferably 120° C. or higher, more preferably 135° C. or higher, further preferably 150° C. or higher, and particularly preferably 161° C. or higher. In addition, from the viewpoint of exhibiting excellent fluidity during molding, the Tg is preferably 180° C. or lower, further preferably 175° C. or lower, and particularly preferably 170° C. or lower.
[0089] In another embodiment of the present invention, from the viewpoint of having excellent heat resistance and excellent fluidity during molding, the (a) Tg range of the N-alkylmaleimide copolymer is preferably 161 to 180°C, more preferably 161 to 175°C, and particularly preferably 161 to 170°C.
[0090] In another embodiment of the present invention, in addition to the above-mentioned conditions (a) and (b), the N-alkylmaleimide copolymer may satisfy the following condition (c).
[0091] (c) It is composed of two or more components having different retention times in a chromatogram of HPLC reverse phase chromatography using a poor solvent and a good solvent as mobile phases, and the ratio of the peak area of the component with a shorter retention time than the good solvent to the sum of all peak areas is 0.0 to 9.0%.
[0092] The HPLC reverse phase chromatography of the present invention is a method for separating / detecting copolymer components in a solution by utilizing the difference in the interaction between the stationary phase and the mobile phase. In the HPLC reverse phase chromatography of the present invention, a chromatographic column with low polarity is used as the stationary phase and a solvent with high polarity is used as the mobile phase, and components with high polarity are separated / detected in order from components with low polarity.
[0093] The packing material of the stationary phase chromatographic column is not particularly limited, but in order to separate / detect the copolymer components with high resolution, a silica gel having surface silanol groups fully supplemented with long-chain alkyl groups is used. Examples of the silica gel having surface silanol groups fully supplemented with long-chain alkyl groups include TSKgel ODS-100V manufactured by Tosoh and TSKgel ODS-100Z manufactured by Tosoh.
[0094] There is no particular limitation on the mobile phase, and in order to separate / detect the copolymer components with high resolution energy, a solvent gradient elution from a poor solvent to a good solvent is performed. Examples of poor solvents include acetonitrile, and examples of good solvents include tetrahydrofuran and chloroform. Examples of gradient elution methods include: when performing separation, the solvent injected into the chromatographic column is changed from a poor solvent to a good solvent. Examples of detectors include: UV detector, UV-VIS detector, diode array detector (DAD), fluorescence (FL) detector, conductivity detector, electrochemical detector (ECD), evaporative light scattering detector (ELSD), and charged aerosol detector (CAD).
[0095] In HPLC reversed phase chromatography, low molecular weight copolymer components tend to have shorter retention times regardless of their polarity. In order to separate / detect copolymer components with high resolution in HPLC reversed phase chromatography, after separation based on molecular weight by GPC, a method of evaluating each separated component by HPLC reversed phase chromatography can be used.
[0096] From the perspective of obtaining an N-alkylmaleimide copolymer having excellent mechanical strength and fluidity during molding, in the UV detector chromatogram of HPLC reverse phase chromatography using a poor solvent and a good solvent as the mobile phase, the ratio of the peak area of the component having a shorter retention time than the good solvent of the N-alkylmaleimide copolymer of one embodiment of the present invention to the sum of all peak areas is preferably in the range of 0.0 to 3.0%, more preferably 0.0 to 1.0%, and particularly preferably 0.0 to 0.5%.
[0097] [Summarize]
[0098] The method for producing an N-alkylmaleimide copolymer according to the first aspect of the present invention comprises: subjecting the following monomers to free radical polymerization, the monomers comprising: 20 to 95% by weight of an N-alkylmaleimide represented by the following formula (1) and 5 to 80% by weight of a styrene compound, the N-alkylmaleimide copolymer having structural units derived from the N-alkylmaleimide and the styrene compound, and when producing the copolymer, dissolving the above monomers and subjecting the above monomers to free radical copolymerization in a polymerization solvent that allows the generated N-alkylmaleimide copolymer to precipitate in the form of particles. In the formula (1), R 1It represents a linear alkyl group having 1 to 12 carbon atoms, a branched alkyl group having 3 to 12 carbon atoms, or a cycloalkyl group having 3 to 6 carbon atoms.
[0099]
[0100] The second aspect of the present invention is a method for producing an N-alkylmaleimide copolymer, comprising: in the first aspect, the R 1 is methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, hexyl, cyclohexyl or octyl.
[0101] The method for producing an N-alkylmaleimide copolymer according to the third aspect of the present invention includes the following steps: in the first aspect or the second aspect, the styrene compound is styrene or α-methylstyrene.
[0102] A fourth aspect of the method for producing an N-alkylmaleimide copolymer of the present invention includes the following steps: in any one of the first to third aspects, wherein the particles of the N-alkylmaleimide polymer produced in the polymerization solvent have an average particle size of 20 to 2000 μm.
[0103] A fifth aspect of the present invention provides a method for producing an N-alkylmaleimide copolymer according to any one of the first to fourth aspects, wherein the polymerization solvent is a mixed solvent containing a water-soluble organic solvent and water, or a mixed solvent containing an aliphatic hydrocarbon and an ester organic solvent.
[0104] A sixth aspect of the present invention provides a method for producing an N-alkylmaleimide copolymer according to the fifth aspect, wherein the polymerization solvent contains 50 to 98% by weight of the water-soluble organic solvent and 2 to 50% by weight of water.
[0105] A seventh aspect of the present invention provides a method for producing an N-alkylmaleimide copolymer, wherein in the fifth aspect, the content of the aliphatic hydrocarbon in the polymerization solvent is 50 to 98% by weight, and the content of the ester organic solvent is 2 to 50% by weight.
[0106] The N-alkylmaleimide copolymer of the eighth embodiment of the present invention comprises 30 to 70% by weight of an N-alkylmaleimide structural unit represented by formula (2), 10 to 40% by weight of a styrene structural unit, and 10 to 40% by weight of a (meth)acrylate structural unit, and satisfies the following conditions (a) and (b):
[0107] (a) Glass transition point (Tg) is 120-180°C;
[0108] (b) The weight average molecular weight (Mw) is 200,000 to 500,000.
[0109]
[0110] In formula (2), R 1 It represents a linear alkyl group having 1 to 12 carbon atoms, a branched alkyl group having 3 to 12 carbon atoms, or a cycloalkyl group having 3 to 6 carbon atoms.
[0111] The N-alkylmaleimide copolymer of the ninth aspect of the present invention satisfies the following condition (c) in the eighth aspect:
[0112] (c) It is composed of two or more components having different retention times in a chromatogram of HPLC reverse phase chromatography using a poor solvent and a good solvent as mobile phases, and the ratio of the peak area of the component having a shorter retention time than the good solvent to the sum of all peak areas is 0.0 to 9.0%.
[0113] In the manufacturing method of this mode, by using a specific polymerization solvent to carry out precipitation polymerization, N- alkylmaleimide copolymers with excellent optical properties and heat resistance can be efficiently manufactured. Specifically, compared to the film formed by the copolymer obtained by the previous suspension polymerization and emulsion polymerization, the transparency of the film formed by the copolymer obtained by the manufacturing method of this mode is more excellent. In addition, the manufacturing method of this mode is simpler to operate than block polymerization, and the same as the film formed by the copolymer obtained by block polymerization, the optical properties (transparency, low birefringence) and heat resistance of the film formed by the copolymer obtained by the manufacturing method of this mode are excellent. Therefore, compared to block polymerization, N- alkylmaleimide copolymers with excellent optical properties and heat resistance can be manufactured more efficiently. The optical properties and heat resistance of the N- alkylmaleimide copolymers obtained by the manufacturing method of one mode of the present invention are excellent, so it can be used for various optical components, optical lenses, optical sheets and optical films.
[0114] As for the N- alkylmaleimide copolymer of one embodiment of the present invention, due to having a specific structure, in addition to optical properties and heat resistance, the fluidity during molding is also excellent. Specifically, the N- alkylmaleimide copolymer of one embodiment of the present invention has a specific range of (a) Tg and (b) Mw, and is an N- alkylmaleimide copolymer with excellent fluidity during molding. In addition, as for the N- alkylmaleimide copolymer of one embodiment of the present invention, due to having a specific composition distribution, it is an N- alkylmaleimide copolymer with excellent mechanical strength and fluidity during molding. Specifically, the content of copolymer components with high polarity and low strength in the N- alkylmaleimide copolymer of one embodiment of the present invention is low. In addition, in one embodiment of the present invention, even if the molecular weight is reduced in order to show fluidity during molding, the strength reduction problem of the N- alkylmaleimide copolymer obtained by block polymerization can be avoided. Therefore, the N- alkylmaleimide copolymer of one embodiment of the present invention is an N- alkylmaleimide copolymer with excellent mechanical strength and fluidity during molding. The N-alkylmaleimide copolymer of one embodiment of the present invention is excellent in not only optical properties and heat resistance but also mechanical strength and flow properties during molding, and therefore can be used for various optical members, optical lenses, optical sheets, and the like obtained by injection molding and extrusion molding.
[0115] The present invention is not limited to the above-described embodiments, and various modifications can be made within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention.
[0116] According to one embodiment of the present invention, an N-alkylmaleimide copolymer having excellent optical properties and heat resistance can be efficiently produced. Therefore, the present invention can be expected to contribute to ensuring consumption and production patterns and achieving sustainable development goals (SDGs) related to industrial infrastructure maintenance.
[0117] Example
[0118] The present invention is described below based on examples, but the present invention is not limited to these examples. It should be noted that, unless otherwise specified, commercially available reagents were used. PerbutylPV of NOF Corporation was used as tert-butyl peroxypivalate. The content of tert-butyl peroxypivalate in Perbutyl PV was 71%. Perhexyl ND of NOF Corporation was used as tert-hexyl peroxyneodecanoate. The content of tert-hexyl peroxyneodecanoate in Perhexyl ND was 71%. Perbutyl O of NOF Corporation was used as tert-butyl peroxy-2-ethylhexanoate. The content of tert-butyl peroxy-2-ethylhexanoate in Perbutyl O was 97%. Metolose (registered trademark) 90SH-100 of Shin-Etsu Chemical Co., Ltd. was used as hydroxypropyl methylcellulose (HPMC).
[0119] The evaluation method and the measurement method of the N-alkylmaleimide copolymer obtained according to the examples are shown below. Next, a specific example of producing the N-alkylmaleimide copolymer is shown.
[0120] [Average particle size]
[0121] 150 mg of particles of the N-alkylmaleimide copolymer produced in each example described below were dispersed in 20 g of ion exchange water and measured using a particle size distribution measuring instrument MT-3300 manufactured by Nikkiso Co., Ltd. The shape was set to be spherical and the refractive index was set to be 1.549.
[0122] [Particle form]
[0123] Using a table microscope TM3030Plus manufactured by Hitachi High-Tech Co., Ltd., the image signal was set to secondary electrons and particles of the N-alkylmaleimide copolymer were observed at a magnification of 30 to 100 times in the standard mode.
[0124] [N-Alkylmaleimide content in polymer]
[0125] A given amount of N-alkylmaleimide copolymer was dissolved in deuterated chloroform (about 5% by weight), and the resulting solution was analyzed using a 400 MHz NMR (JNM-ECZ400S / L1) manufactured by JEOL Ltd. 1 H-NMR measurement: Regarding the copolymer of N-alkylmaleimide and a styrene compound, the content of the structure derived from N-alkylmaleimide (RMI unit, wt%) was calculated from the integrated ratio of the peak between 5.0 and 0.3 ppm to the peak between 8.0 and 5.5 ppm.
[0126] [Weight average molecular weight Mw and molecular weight distribution Mw / Mn of polymer]
[0127] The molecular weight distribution of the N-alkylmaleimide copolymer was measured using a Tosoh GPC (HLC-8320GPC). Two Tosoh TSKgel Super HM-H columns were used for the test. The column temperature was set at 40°C and tetrahydrofuran was used as the eluent. The molecular weight calibration curve was prepared using Tosoh standard polystyrene with known molecular weight.
[0128] [Film making]
[0129] The N-alkylmaleimide copolymer was dissolved in 10 times the amount of dichloromethane, and the obtained polymer solution was spread on a PET film using a coater. The PET film after the polymer solution was spread was covered with a lid, and the film of the N-alkylmaleimide copolymer formed on the PET film after the solvent was slowly evaporated was peeled off and dried under reduced pressure in a reduced pressure dryer set at 105° C. for 24 hours.
[0130] [Solubility]
[0131] The N-alkylmaleimide copolymer was dissolved in 10-fold amount of chloroform, and the appearance of the obtained polymer solution was visually observed to evaluate whether there was an insoluble portion.
[0132] [film thickness]
[0133] The film thickness of the film produced in the above-mentioned "Film Formation" was measured using a micrometer.
[0134] [Glass transition point (Tg)]
[0135] The glass transition point (Tg) of the film obtained in the above "Film Formation" was measured at the second scanning temperature increase (temperature increase rate = 10°C / min) using a differential scanning calorimeter DSC-60 manufactured by Shimadzu Corporation.
[0136] [Photoelastic constant C]
[0137] The measurement was performed using an automatic birefringence control device ABR-EX manufactured by Uniopt. A stress of 0 to 2 N was applied in stages from weak to strong at intervals of about 0.1 N to the film having a width of 4 to 5 mm and a thickness of 35 to 55 μm prepared by the "film preparation" described above, and the phase difference was measured. The photoelastic constant C of the film was calculated from the phase difference and the width of the measured portion within the range of 0.3 to 2 N.
[0138] [Intrinsic birefringence]
[0139] The film produced by the above "film production" was subjected to single screw stretching using a twin-screw stretching device IMC-11A9 manufactured by Imoto Manufacturing Co., Ltd. at a temperature above Tg, a stretching speed of 40 to 100 mm / min, and a stretching ratio of 2 to 3 times. Thereafter, the obtained stretched film was allowed to stand for more than 24 hours to relax the internal stress of the stretched film, and then the absorbance of the stretched film in the infrared region was measured using a Fourier transform infrared spectrophotometer IRTracer-100 manufactured by Shimadzu Corporation.
[0140] The orientation degree f of each stretched film was evaluated based on the absorbance after measurement using infrared dichroism. In addition, the thickness d of each stretched film was measured using a screw micrometer. In addition, the phase difference Re of each stretched film was measured using the automatic birefringence control device ABR-10A manufactured by Uniopt. Based on the orientation degree f, thickness d, and phase difference Re of the stretched film, the intrinsic birefringence Δn was calculated using the following formula (3). 0 .
[0141] Re=Δn 0 ·f·d (3)
[0142] [Temperature constant of intrinsic birefringence]
[0143] The stretched film prepared by the above-mentioned "intrinsic birefringence" was heated from 15°C to 70°C in increments of 5°C. The phase difference of the stretched film at each temperature was measured using an automatic birefringence control device ABR-10A manufactured by Uniopt, and the temperature constant dΔn of the intrinsic birefringence was calculated. 0 / dT.
[0144] [GPC-based extraction]
[0145] According to the molecular weight of the N-alkylmaleimide copolymer, the extraction was performed using a GPC (LaboACELC-7080) manufactured by Japan Analytical Industry. Two TSKgel GMHHR-H manufactured by Tosoh were used as the chromatographic column, the column temperature was set to 25°C, the flow rate was set to 6 mL / min., tetrahydrofuran was used as the eluent, and 2 mL of a tetrahydrofuran solution (5 mg / mL) of the N-alkylmaleimide copolymer was injected each time, and the mixture was fractionated into 5 components with different molecular weights. Using a GPC (HLC-8320GPC) manufactured by Tosoh, two TSKgel GMHHR-H manufactured by Tosoh were used as the chromatographic column, the column temperature was set to 40°C, the flow rate was set to 1 mL / min., tetrahydrofuran was used as the eluent, and 100 μL of a tetrahydrofuran solution (1 mg / mL) of each extract was injected each time, and the molecular weight of each extract obtained was confirmed and evaluated.
[0146] [HPLC reverse phase chromatography]
[0147] Using HPLC (Prominence HPLC system) manufactured by Shimadzu Corporation, each GPC separation extract after fractionation was measured. The stationary phase chromatographic column used was TSKgel ODS-100V manufactured by Tosoh, the column temperature was set to 40°C, the flow rate was set to 1 mL / min., acetonitrile was used as the poor solvent for the mobile phase, and tetrahydrofuran was used as the good solvent. The GPC separation extract was dissolved in tetrahydrofuran (1 mg / mL), and 10 μL was injected into the stationary phase chromatographic column filled with acetonitrile to precipitate in the stationary phase chromatographic column. After acetonitrile was injected into the chromatographic column for 10 minutes, it was replaced with tetrahydrofuran and injected for another 5 minutes, and the separation evaluation was performed to obtain a chromatogram using a UV detector. Tetrahydrofuran used to dissolve the GPC separation extract / fill the stationary phase chromatographic column was detected at a retention time of 1.9 minutes. As a component derived from the GPC separation extract, in addition to a shorter retention time (1.1 minutes) than tetrahydrofuran, peaks were detected near retention time = 2 minutes and 5.8 minutes. For all the GPC separated extracts, the peak areas of the respective peaks were summed to calculate the ratio of the peak area of the component having a retention time shorter than that of tetrahydrofuran to the sum of all the peak areas (excluding the tetrahydrofuran peak).
[0148] [Example 1]
[0149] In a 500 mL four-necked flask equipped with a stirrer, a nitrogen inlet tube, and a thermometer, 296.9 g of methanol, 33.0 g of distilled water, 18.0 g of styrene, 72.3 g of N-ethylmaleimide, and 409 mg of tert-hexyl peroxyneodecanoate were added, and nitrogen was bubbled in for 1 hour. Then, the contents of the four-necked flask were heated to 40° C. while stirring at 400 rpm to start precipitation polymerization. As the polymerization time passed, precipitation of a particulate copolymer was observed.
[0150] After 10 hours, the contents were introduced into 2000g of distilled water stirred with a magnetic stirrer, and the generated N-alkylmaleimide copolymer particles were recovered by filtration. It was confirmed that 1.8g of amorphous copolymer was attached to the inner wall of the flask and the stirring blade / stirring shaft. The copolymer particles recovered in particle form were washed twice with 2000g of distilled water, and then washed three times with 1584g of methanol. The washed copolymer particles were placed in a dryer set at 95°C and dried under vacuum. The drying was stopped at the time point when the weight loss caused by drying stopped, and 59.46g of N-ethylmaleimide / styrene copolymer was obtained. The result of screening was that all particles passed through a sieve with a mesh size of 2mm, but 0.13g of particles remained on a sieve with a mesh size of 1mm.
[0151] [Example 2]
[0152] Methanol 296.8g, distilled water 33.0g, styrene 18.8g, N-ethylmaleimide 71.5g, and peroxy neodecanoic acid tert-hexyl ester 410mg were used, and precipitation polymerization was carried out by the same method as Example 1. It was confirmed that 1.8g of amorphous copolymer was attached to the inner wall of the flask and the stirring blade / stirring shaft. On the other hand, 66.6g of particulate N-ethylmaleimide / styrene copolymer was obtained. As a result of screening, all particles passed through a sieve with a mesh size of 2mm, but 2.69g of particles remained on a sieve with a mesh size of 1mm.
[0153] [Example 3]
[0154] Methanol 296.4g, distilled water 32.9g, styrene 25.4g, N-ethylmaleimide 64.8g, and peroxy neodecanoic acid tert-hexyl ester 415mg were used, and precipitation polymerization was carried out by the same method as in Example 1. It was confirmed that 1.6g of amorphous copolymer was attached to the inner wall of the flask and the stirring blade / stirring shaft. On the other hand, 66.5g of particulate N-ethylmaleimide / styrene copolymer was obtained. As a result of screening, all particles passed through a sieve with a mesh size of 2mm, but 30.2g of particles remained on a sieve with a mesh size of 1mm.
[0155] [Example 4]
[0156] Methanol 295.4g, distilled water 32.8g, styrene 40.8g, N-ethylmaleimide 49.1g, and peroxy neodecanoic acid tert-hexyl ester 427mg were used, and precipitation polymerization was carried out by the same method as in Example 1. It was confirmed that 5.1g of amorphous copolymer was attached to the inner wall of the flask and the stirring blade / stirring shaft. On the other hand, 82.8g of particulate N-ethylmaleimide / styrene copolymer was obtained. As a result of screening, all particles passed through a sieve with a mesh size of 2mm, but 36.7g of particles remained on a sieve with a mesh size of 1mm.
[0157] [Example 5]
[0158] Methanol 282.4g, distilled water 49.8g, styrene 25.6g, N-ethylmaleimide 65.4g, and peroxy neodecanoic acid tert-hexyl ester 419mg were used, and precipitation polymerization was carried out by the same method as in Example 1. It was confirmed that 2.6g of amorphous copolymer was attached to the inner wall of the flask and the stirring blade / stirring shaft. On the other hand, 66.7g of particulate N-ethylmaleimide / styrene copolymer was obtained. As a result of screening, all particles passed through a sieve with a mesh size of 2mm, but 37.0g of particles remained on a sieve with a mesh size of 1mm.
[0159] [Example 6]
[0160] Methanol 268.1g, distilled water 67.0g, styrene 25.8g, N-ethylmaleimide 66.0g, and peroxy neodecanoic acid tert-hexyl ester 422.5mg were used, and precipitation polymerization was carried out by the same method as in Example 1. It was confirmed that 2.6g of amorphous copolymer was attached to the inner wall of the flask and the stirring blade / stirring shaft. On the other hand, 66.4g of particulate N-ethylmaleimide / styrene copolymer was obtained. As a result of screening, all particles passed through a sieve with a mesh size of 2mm, but 37.0g of particles remained on a sieve with a mesh size of 1mm.
[0161] [Example 7]
[0162] Methanol 253.6g, distilled water 84.5g, styrene 26.1g, N-ethylmaleimide 66.5g, and peroxy neodecanoic acid tert-hexyl ester 426mg were used, and precipitation polymerization was carried out by the same method as in Example 1. It was confirmed that 32.9g of amorphous copolymer was attached to the inner wall of the flask and the stirring blade / stirring shaft. On the other hand, 39.1g of particulate N-ethylmaleimide / styrene copolymer was obtained. As a result of screening, all particles passed through a sieve with a mesh size of 2mm, but 1.9g of particles remained on a sieve with a mesh size of 1mm.
[0163] [Example 8]
[0164] The precipitation polymerization was carried out in the same manner as in Example 1 except that 268.1 g of methanol, 67.0 g of distilled water, 25.8 g of styrene and 66.0 g of N-ethylmaleimide were used, 270 mg of tert-butyl peroxypivalate was used as a polymerization initiator, and the polymerization temperature was set to 50°C. It was confirmed that 43.0 g of amorphous copolymer was attached to the inner wall of the flask and the stirring blade / stirring shaft. On the other hand, 27.9 g of particulate N-ethylmaleimide / styrene copolymer was obtained. As a result of sieving, all particles passed through a sieve with a mesh size of 2 mm, but 7.7 g of particles remained on a sieve with a mesh size of 1 mm.
[0165] [Example 9]
[0166] Except for using 160.9 g of methanol, 40.2 g of distilled water, 15.5 g of styrene, 39.6 g of N-ethylmaleimide, and 162 mg of tert-butyl peroxypivalate, precipitation polymerization was carried out in the same manner as in Example 8. It was confirmed that 23.4 g of amorphous copolymer adhered to the inner wall of the flask and the stirring blade / stirring shaft. On the other hand, 19.2 g of particulate N-ethylmaleimide / styrene copolymer was obtained.
[0167] [Example 10]
[0168] Except for using 125.0 g of methanol, 83.4 g of distilled water, 16.1 g of styrene, 41.0 g of N-ethylmaleimide, and 168 mg of tert-butyl peroxypivalate, precipitation polymerization was carried out in the same manner as in Example 8. It was confirmed that 28.8 g of amorphous copolymer adhered to the inner wall of the flask and the stirring blade / stirring shaft. On the other hand, 13.6 g of particulate N-ethylmaleimide / styrene copolymer was obtained.
[0169] [Example 11]
[0170] Methanol 284.9g, distilled water 31.7g, styrene 29.7g, N-ethylmaleimide 75.8g, and peroxy neodecanoic acid tert-hexyl ester 486mg were used, and precipitation polymerization was carried out by the same method as Example 1. It was confirmed that 12.5g of amorphous copolymer was attached to the inner wall of the flask and the stirring blade / stirring shaft. On the other hand, 69.7g of particulate N-ethylmaleimide / styrene copolymer was obtained. As a result of screening, all particles passed through a sieve with a mesh size of 2mm, but 6.4g of particles remained on a sieve with a mesh size of 1mm.
[0171] [Example 12]
[0172] Methanol 268.6g, distilled water 51.2g, styrene 30.0g, N-ethylmaleimide 76.6g, and peroxy neodecanoic acid tert-hexyl ester 491mg were used, and precipitation polymerization was carried out by the same method as in Example 1. It was confirmed that 37.9g of amorphous copolymer was attached to the inner wall of the flask and the stirring blade / stirring shaft. On the other hand, 44.9g of particulate N-ethylmaleimide / styrene copolymer was obtained. As a result of screening, all particles passed through a sieve with a mesh size of 2mm, but 5.5g of particles remained on a sieve with a mesh size of 1mm.
[0173] [Example 13]
[0174] In a 50 mL glass reaction container, 16.4 g of methylcyclohexane, 7.0 g of butyl acetate, 1.8 g of styrene, and 4.6 g of N-ethylmaleimide were added, and nitrogen was bubbled for 50 minutes. Then, 29.6 mg of tert-hexyl peroxy neodecanoate was added, and nitrogen was further bubbled for 10 minutes. The mixture was stirred at 600 rpm using a magnetic stirrer, and the mixture was kept at 40 ° C for 10 hours, thereby performing precipitation polymerization. After the precipitation polymerization was completed, the contents were introduced into 200 mL of methanol, and the generated N-alkylmaleimide copolymer particles were recovered by filtration. It was confirmed that 0.29 g of amorphous copolymer was attached to the inner wall of the flask. The polymer particles recovered in the form of particles were washed twice with 200 mL of methanol. The washed polymer particles were added to a dryer set at 95 ° C and dried under vacuum. The drying was stopped at the time point when the weight loss caused by drying stopped, and 5.5 g of N-ethylmaleimide / styrene copolymer was obtained.
[0175] [Example 14]
[0176] In a 500mL 4-necked flask equipped with a stirrer, a nitrogen inlet tube and a thermometer, 292.3g of methylcyclohexane, 32.5g of butyl acetate, 13.8g of styrene, 16.3g of methyl methacrylate and 51.2g of N-ethylmaleimide were added, and nitrogen was bubbled for 50 minutes, and then 272.4mg of tert-hexyl peroxy neodecanoate was added, and nitrogen was further bubbled for 10 minutes. Then, a magnetic stirrer was used to stir at 400rpm while maintaining at 40°C for 10 hours, thereby performing precipitation polymerization. After the precipitation polymerization was completed, the contents were introduced into 2L of methanol, and the generated N-alkylmaleimide copolymer particles were recovered by filtration. It was confirmed that 3.57g of amorphous copolymer was attached to the inner wall of the flask. The polymer particles recovered in particle form were washed twice with 2L of methanol. Drying was stopped at the time point when the weight loss due to drying stopped, and 71.5g of N-ethylmaleimide / styrene / methyl methacrylate copolymer was obtained. The obtained particulate N-alkylmaleimide copolymer had Tg = 171.0°C and Mw = 290,000. GPC was used for separation and extraction to obtain a component with Mw = 960,000 (fraction 1), a component with Mw = 490,000 (fraction 2), a component with Mw = 200,000 (fraction 3), a component with Mw = 74,000 (fraction 4), and a component with Mw = 25,000 (fraction 5). The HPLC reverse chromatogram of each separated extract was evaluated, and three copolymer components with retention times = 1.1 minutes, 2.0 minutes, and 5.8 minutes were confirmed in the UV detector chromatogram and the ELSD chromatogram. The peak areas of all the peaks of the GPC separated extracts were evaluated and summed, and the sum of the peak areas of components with a retention time shorter than that of tetrahydrofuran (retention time = 1.9 minutes in the UV detector chromatogram, not detected in the ELSD chromatogram) was 1.0% of the sum of all the peak areas (excluding tetrahydrofuran).
[0177] [Example 15]
[0178] In a 200 mL glass reaction container, 58.0 g of methylcyclohexane, 6.4 g of dimethyl carbonate, 5.0 g of styrene, and 12.7 g of N-ethylmaleimide were added, and nitrogen was bubbled for 50 minutes. Then, 81.3 mg of tert-hexyl peroxy neodecanoate was added, and nitrogen was further bubbled for 10 minutes. Then, a magnetic stirrer was used to stir at 600 rpm, and the mixture was kept at 40°C for 10 hours, thereby performing precipitation polymerization. After the precipitation polymerization was completed, the contents were introduced into 500 mL of methanol, and the generated N-alkylmaleimide copolymer particles were recovered by filtration. It was confirmed that 8.3 g of amorphous copolymer was attached to the inner wall of the flask. The polymer particles recovered in the form of particles were washed twice with 500 mL of methanol. The washed polymer particles were added to a dryer set at 95°C and dried under vacuum. The drying was stopped at the time point when the weight loss caused by drying stopped, and 7.8 g of N-ethylmaleimide / styrene copolymer was obtained.
[0179] [Example 16]
[0180] A 3L four-necked flask equipped with a stirrer, a nitrogen inlet tube and a thermometer was used to add 1747.38g of methylcyclohexane, 194.78g of butyl acetate, 98.04g of styrene, 111.54g of methyl methacrylate and 277.22g of N-ethylmaleimide. After bubbling nitrogen for 110 minutes, 831mg of tert-hexyl peroxyneodecanoate was added, and nitrogen was further bubbled for 10 minutes. Then, the mixture was kept at 40°C for 24 hours while stirring at 167rpm, thereby performing precipitation polymerization. After the precipitation polymerization was completed, the contents were introduced into 2L of methanol, and the generated N-alkylmaleimide copolymer particles were recovered by filtration. It was confirmed that 13.36g of amorphous copolymer was attached to the inner wall of the flask, the stirring rod and the thermometer. The polymer particles recovered in the form of particles were washed three times with 2L of methanol. The washed polymer particles were added to a dryer set at 95°C and dried under vacuum. Drying was stopped at the time point when the weight loss due to drying stopped, and 433.9g of N-ethylmaleimide / styrene / methyl methacrylate copolymer was obtained. The obtained particulate N-alkylmaleimide copolymer had Tg = 165.0°C and Mw = 289,000. GPC was used for separation and extraction to obtain a component with Mw = 1.07 million (fraction 1), a component with Mw = 520,000 (fraction 2), a component with Mw = 200,000 (fraction 3), a component with Mw = 65,000 (fraction 4), and a component with Mw = 19,000 (fraction 5). The HPLC reverse chromatogram of each separated extract was evaluated, and two copolymer components with retention times = 2.0 minutes and 5.8 minutes were confirmed in the UV detector chromatogram and the ELSD chromatogram. No component having a retention time shorter than tetrahydrofuran (UV detector chromatogram retention time = 1.9 minutes, not detected in the ELSD chromatogram) was detected, and by evaluating and summing the peak areas of the peaks in all GPC separation extracts, the sum of the peak areas of components having a retention time shorter than tetrahydrofuran was 0.0% of the sum of all peak areas (excluding tetrahydrofuran).
[0181] [Comparative Example 1]
[0182] Add 3.8g of N-ethylmaleimide and 1.2g of styrene to a test tube and mix. After sealing the test tube, mix the contents by sufficient shaking. Allow the test tube to stand in a hot water bath at 70°C for 24 hours to perform block polymerization. The obtained N-alkylmaleimide copolymer is a cylindrical block adhered to the test tube. In order to remove the unreacted monomers, the cylindrical block is taken out from the test tube, crushed into about 1 cm square at a time, and put into dichloromethane to prepare a transparent N-alkylmaleimide copolymer solution. Thereafter, the obtained N-alkylmaleimide copolymer solution is dripped into methanol to precipitate the N-alkylmaleimide copolymer. Filter with filter paper, after removing the filtrate dissolved with the unreacted monomers, recover the remaining N-alkylmaleimide copolymer on the filter paper, and dry it under reduced pressure in a desiccator for 3 hours. Thereafter, the mixture was further dried under reduced pressure in a reduced pressure dryer at 105° C. for 24 hours to obtain 4.0 g of an N-alkylmaleimide copolymer. The particle morphology of the N-alkylmaleimide copolymer particles was visually observed to be amorphous.
[0183] [Comparative Example 2]
[0184] Add 6.1g of N-ethylmaleimide, 2.7g of styrene, 35.4g of toluene, and 19.0mg of tert-butyl peroxypivalate to a 75mL ampoule tube, degas the ampoule tube, and melt and seal the ampoule tube through a burner. The sealed ampoule tube is placed in a hot water bath (set to 50°C) attached to an oscillator and shaken for 10 hours to perform solution polymerization. The resulting product is put into 400mL of chloroform to prepare a transparent N-alkylmaleimide copolymer solution. Thereafter, the resulting N-alkylmaleimide copolymer solution is dripped into methanol to precipitate the N-alkylmaleimide copolymer. Filter with filter paper, recover the N-alkylmaleimide copolymer remaining on the filter paper, and dry it under reduced pressure in a reduced pressure dryer set at 95°C for 10 hours to obtain 7.9g of N-alkylmaleimide copolymer. The particle morphology of the N-alkylmaleimide copolymer particles was visually observed to be amorphous.
[0185] [Comparative Example 3]
[0186] In a 500mL four-necked flask equipped with a stirrer, a nitrogen inlet tube and a thermometer, 0.852g of hydroxypropylmethylcellulose (HPMC), 346.4g of distilled water, 103.9g of N-ethylmaleimide, 25.8g of styrene, 18.4g of toluene, and 100mg of tert-butyl peroxy 2-ethylhexanoate were added, and nitrogen was bubbled for 1 hour, and then kept at 70°C for 2 hours while stirring at 600rpm, thereby performing suspension polymerization. After the suspension polymerization was completed, the content was introduced into 2500g of distilled water stirred with a magnetic stirrer, and the generated N-alkylmaleimide copolymer particles were recovered by filtration. The recovered polymer particles were washed 6 times with 2000g of distilled water, and then washed 5 times with 1582g of methanol. Thereafter, they were washed once with a mixed solvent of 487g of toluene and 1137g of methanol, and then washed 5 times with 1582g of methanol. Furthermore, the polymer particles were washed once with a mixed solvent of 827 g of toluene and 827 g of methanol, and then washed five times with 1582 g of methanol. The washed polymer particles were placed in a dryer set at 95° C. and dried under vacuum. Drying was stopped at the time when the weight loss due to drying stopped, and 67.5 g of N-ethylmaleimide / styrene copolymer was obtained.
[0187] [Comparative Example 4]
[0188] Except that 194.2 g of methanol, 15.0 g of styrene, 38.2 g of N-ethylmaleimide, and 157 mg of tert-butyl peroxypivalate were used and no water was used, precipitation polymerization was carried out in the same manner as in Example 8. It was confirmed that 29.9 g of amorphous copolymer adhered to the inner wall of the flask and the stirring blade / stirring shaft. On the other hand, 7.5 g of particulate N-ethylmaleimide / styrene copolymer was obtained.
[0189] [Comparative Example 5]
[0190] 3.15 g of N-ethylmaleimide, 0.85 g of styrene, and 1.0 g of methyl methacrylate were added to a test tube, and bulk polymerization was carried out by the same method as in Comparative Example 1 to obtain 4.0 g of an N-alkylmaleimide copolymer. The obtained N-alkylmaleimide copolymer had a Tg of 165.0°C and a Mw of 1.09 million. By separation and extraction using GPC, a component with Mw of 2.94 million (fraction 1), a component with Mw of 2.12 million (fraction 2), a component with Mw of 1.15 million (fraction 3), a component with Mw of 440,000 (fraction 4), and a component with Mw of 120,000 (fraction 5) were obtained. The HPLC reverse chromatogram of each separated extract was evaluated in the same manner as in Example 16, and three copolymer components with retention times of 1.1 minutes, 2.0 minutes, and 7 to 8 minutes were confirmed in the UV detector chromatogram. By summing the peak areas of the respective peaks of all GPC separation extracts, the sum of the peak areas of components having a retention time shorter than tetrahydrofuran (retention time = 1.9 minutes) was 10% of the sum of all peak areas (excluding tetrahydrofuran).
[0191] [Reference Example 1]
[0192] The HPLC reverse phase chromatography of N-ethylmaleimide homopolymer, styrene homopolymer, methyl methacrylate homopolymer and N-ethylmaleimide / styrene alternating copolymer was evaluated. As a result, in the UV detector chromatogram, EMI homopolymer showed a peak at retention time = 1.1 minutes. In addition, styrene homopolymer showed a peak at 11 minutes. In addition, methyl methacrylate homopolymer showed a peak at 7 to 8 minutes. In addition, N-ethylmaleimide / styrene alternating copolymer showed a peak at 2 minutes. It can be seen that the component with a peak at retention time = 1.1 minutes in the N-alkylmaleimide copolymer is a polymer showing a polarity close to that of the EMI homopolymer having a peak at substantially the same retention time.
[0193] Regarding the above-mentioned examples and comparative examples, Tables 1 and 2 show the addition compositions of monomers and polymerization solvents in the manufacture of N-alkylmaleimide copolymer particles, respectively, and Table 3 shows the addition composition of initiators and manufacturing conditions. In addition, regarding the above-mentioned examples and comparative examples, Table 4 shows the results of the manufacture of N-alkylmaleimide copolymer particles. In addition, regarding the above-mentioned examples and comparative examples, Table 5 shows the solubility of the obtained N-alkylmaleimide copolymer in chloroform, as well as film properties such as film thickness, heat resistance, photoelastic constant, intrinsic birefringence, and temperature constant of intrinsic birefringence. In Tables 4 and 5, the numerical values of non-characteristic data are omitted and left blank.
[0194] It should be noted that, in the table, "RMI" represents N-alkylmaleimide, "St" represents a styrene compound (styrene), "EMI" represents N-ethylmaleimide, "MMA" represents methyl methacrylate, and "MCH" represents methylcyclohexane. In addition, in Table 2, the solvent B "water" in Comparative Example 3 a) " means that 0.0085 parts by weight of hydroxypropylmethylcellulose is contained in the water of solvent B as a dispersant.
[0195]
[0196]
[0197] [Table 3]
[0198]
[0199]
[0200] [Table 5]
[0201]
[0202] [Investigation]
[0203] It is understood that in the examples, a sufficient amount of N-alkylmaleimide-based copolymer was generated as particles, and the polymerization solvent in the examples is sufficiently useful as a polymerization solvent for precipitation polymerization in the production of a copolymer of N-alkylmaleimide and a styrene compound.
[0204] From the comparison between Examples 1 to 3 and Example 4, it can be seen that the yield of deposits becomes lower by further increasing the amount of N-ethylmaleimide added.
[0205] From the comparison between Example 3 and Example 5, the comparison between Example 5 and Example 6, the comparison between Example 6 and Example 7, and the comparison between Example 9 and Example 10, it can be seen that by further reducing the mixing ratio of distilled water in the methanol / distilled water mixed solvent, the yield of attached matter becomes lower.
[0206] From the comparison between Example 6 and Example 8, it can be seen that by changing the polymerization initiator from tert-hexyl peroxyneodecanoate to tert-butyl peroxypivalate and increasing the polymerization temperature from 40° C. to 50° C., the yield of the deposits increases.
[0207] From the comparison between Example 3 and Example 11, and the comparison between Example 5 and Example 12, it can be seen that the yield of deposits is further reduced by reducing the monomer concentration (RMI+St).
[0208] According to Example 13, the methylcyclohexane / butyl acetate mixed solvent can also effectively control the yield of the attached matter.
[0209] According to Example 14, good fluidity during molding can be obtained from the Tg and Mw of the obtained N-alkylmaleimide copolymer. In addition, the N-alkylmaleimide copolymer is composed of three copolymer components having different retention times in HPLC reverse phase chromatography, and the ratio of the peak area of the component having a shorter retention time than tetrahydrofuran (UV detector chromatogram retention time = 1.9 minutes, not detected in ELSD chromatogram) to the sum of all peak areas is in the range of 0.0 to 9.0%, and the components causing strength reduction are reduced.
[0210] According to Example 15, the methylcyclohexane / dimethyl carbonate mixed solvent can also effectively control the yield of the attached matter.
[0211] According to Example 16, good fluidity during molding can be obtained from the Tg and Mw of the obtained N-alkylmaleimide copolymer. In addition, the N-alkylmaleimide copolymer is composed of two copolymer components having different retention times in HPLC reverse phase chromatography, and no component having a retention time shorter than tetrahydrofuran (UV detector chromatogram retention time = 1.9 minutes, not detected in ELSD chromatogram) is detected, and no component causing strength reduction is included.
[0212] Comparative Example 1 is an example of producing an N-alkylmaleimide copolymer by block polymerization. In Comparative Example 1, since the copolymer produced is a block, it is necessary to perform steps of crushing the block, dissolving it in a solvent, and precipitating the copolymer in a solvent that dissolves unreacted monomers.
[0213] Comparative Example 2 is an example of producing an N-alkylmaleimide copolymer by solution polymerization. In Comparative Example 2, since the produced copolymer is dissolved in the polymerization solvent, a step of precipitating the copolymer in a solvent that dissolves unreacted monomers is required.
[0214] Comparative Example 3 is an example of producing an N-alkylmaleimide copolymer by suspension polymerization. In Comparative Example 3, since the produced copolymer contained a residual dispersant and contained an insoluble substance (gel) when dissolved in chloroform, a step of removing the gel was required before forming a transparent film.
[0215] In Comparative Example 4, compared with Examples 9 and 10, by changing the polymerization solvent from a methanol / distilled water mixed solvent to a single methanol solvent, the yield of deposits was further increased compared with the Examples.
[0216] Comparative Example 5 is a manufacturing example of an N-alkylmaleimide copolymer based on block polymerization. In order to exhibit good fluidity during molding, it is necessary to reduce the Mw of the obtained N-alkylmaleimide copolymer. In addition, the N-alkylmaleimide copolymer is composed of three copolymer components with different retention times in HPLC reverse phase chromatography, and the ratio of the copolymer component with a retention time shorter than that of tetrahydrofuran to the N-alkylmaleimide copolymer exceeds 9.0%, and the components that cause strength reduction are increased. In order to exhibit good fluidity during molding, when the molecular weight is reduced, the reduction in strength becomes significant.
[0217] From the results of evaluating the HPLC reverse phase chromatography of the N-ethylmaleimide homopolymer, styrene homopolymer, methyl methacrylate homopolymer and N-ethylmaleimide / styrene alternating copolymer of Reference Example 1, it can be seen that in the N-alkylmaleimide-based copolymers obtained according to Example 14 and Comparative Example 5, the component with a retention time shorter than that of tetrahydrofuran is a polymer showing a polarity close to that of the EMI homopolymer, and the component with a retention time shorter than that of tetrahydrofuran has a peak at substantially the same retention time as that of the EMI homopolymer.
[0218] Industrial Applicability
[0219] The present invention can be used for materials for producing various optical members (optical lenses, optical sheets, optical films, etc.) having excellent optical properties and heat resistance.
Claims
1. A method for producing an N-alkylmaleimide copolymer, the method comprising: A monomer is subjected to free radical copolymerization, wherein the monomer comprises: 20 to 95% by weight of an N-alkyl maleimide represented by the following formula (1) and 5 to 80% by weight of a styrene compound; In formula (1), R 1 represents a linear alkyl group having 1 to 12 carbon atoms, a branched alkyl group having 3 to 12 carbon atoms, or a cycloalkyl group having 3 to 6 carbon atoms, When producing the N-alkylmaleimide copolymer having structural units derived from the N-alkylmaleimide and the styrene compound, the monomers are radically copolymerized in a polymerization solvent in which the monomers are dissolved and the produced N-alkylmaleimide copolymer is precipitated in the form of particles.
2. The method for producing an N-alkylmaleimide copolymer according to claim 1, wherein: The R 1 It is methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, hexyl, cyclohexyl or octyl.
3. The method for producing an N-alkylmaleimide copolymer according to claim 1 or 2, wherein: The styrene compound is styrene or α-methylstyrene.
4. The method for producing an N-alkylmaleimide copolymer according to claim 1 or 2, wherein: The average particle size of the particles of the N-alkylmaleimide polymer produced in the polymerization solvent is 20 to 2000 μm.
5. The method for producing an N-alkylmaleimide copolymer according to claim 1 or 2, wherein: The polymerization solvent is a mixed solvent containing a water-soluble organic solvent and water, or a mixed solvent containing an aliphatic hydrocarbon and an ester-based organic solvent.
6. The method for producing an N-alkylmaleimide copolymer according to claim 5, wherein: In the polymerization solvent, the content of the water-soluble organic solvent is 50 to 98% by weight, and the content of water is 2 to 50% by weight.
7. The method for producing an N-alkylmaleimide copolymer according to claim 5, wherein: In the polymerization solvent, the content of the aliphatic hydrocarbon is 50 to 98% by weight, and the content of the ester organic solvent is 2 to 50% by weight.
8. An N-alkylmaleimide-based copolymer, comprising: 30 to 70% by weight of the N-alkylmaleimide structural unit represented by formula (2), 10 to 40% by weight of styrene structural units, and (Meth)acrylate structural units 10-40% by weight, in, The copolymer satisfies the following conditions (a) and (b): (a) Glass transition point (Tg) is 120-180°C; (b) a weight average molecular weight (Mw) of 200,000 to 500,000, In formula (2), R 1 It represents a linear alkyl group having 1 to 12 carbon atoms, a branched alkyl group having 3 to 12 carbon atoms, or a cycloalkyl group having 3 to 6 carbon atoms.
9. The N-alkylmaleimide copolymer according to claim 8, further satisfying the following condition (c): (c) It is composed of two or more components having different retention times in a chromatogram of HPLC reverse phase chromatography using a poor solvent and a good solvent as mobile phases, and the ratio of the peak area of the component having a shorter retention time than the good solvent to the sum of all peak areas is 0.0 to 9.0%.
Citation Information
Patent Citations
Production of copolymer
JP1993194609A
Manufacture of copolymer
JP1993209004A
Copolymer production method
JP1993247145A
Optical polymer material, optical film, display device, optical polymer material manufacturing method, and optical film manufacturing method
JP2020126229A